Gaining Knowledge through Understanding Distress and Positive Factors in Social Environments - Petrič Karl (European Review Of Applied Sociology)
This research examines the opinions of public sector representatives regarding the distress they experience in everyday life. By identifying sources of stress, positive factors, and suggestions for stress reduction from various social environments, valuable data can be gathered and converted into knowledge. Determining the power of distress and estimating energy consumption (in kilocalories) in diverse social (work) environments can provide management, including politicians and leaders in work organizations, with insight into disruptive factors within various social (work) processes. This serves as a psychosocial barometer, reminding us that sensible decisions and corrective action may be necessary. The study presents estimates of distress power and energy consumption in kilocalories based on the opinions of civil servants in their everyday lives.